2018
DOI: 10.3390/s18113720
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experimental Evaluation of an Odor Sensing Method for a Pocket-Sized Quadcopter

Abstract: In this study, we design and verify an intake system using the wake of a pocket-sized quadcopter for the chemical plume tracing (CPT) problem. Solving CPT represents an important technique in the field of engineering because it can be used to perform rescue operations at the time of a disaster and to identify sources of harmful substances. An appropriate intake of air when sensing odors plays an important role in performing CPT. Hence, we used the air flow generated by a quadcopter itself to intake chemical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 55 publications
0
26
0
1
Order By: Relevance
“…1 The authors are with the Distributed Intelligent Systems and Algorithms Laboratory, School of Architecture, Civil and Environmental Engineering,École Polytechnique Fédérale de Lausanne (EPFL), 1015 Lausanne, Switzerland effect on the plume of the gas, making its detection a challenging task [4], [5], [6].In order to avoid the effect of the wake, Neumann et al [7] proposed a robotic platform for aerial sensing that uses remote gas sensors. However, the start-stop strategy for gas detection proposed in this paper does not allow continuous detection and drains the battery quickly.…”
Section: Introductionmentioning
confidence: 99%
“…1 The authors are with the Distributed Intelligent Systems and Algorithms Laboratory, School of Architecture, Civil and Environmental Engineering,École Polytechnique Fédérale de Lausanne (EPFL), 1015 Lausanne, Switzerland effect on the plume of the gas, making its detection a challenging task [4], [5], [6].In order to avoid the effect of the wake, Neumann et al [7] proposed a robotic platform for aerial sensing that uses remote gas sensors. However, the start-stop strategy for gas detection proposed in this paper does not allow continuous detection and drains the battery quickly.…”
Section: Introductionmentioning
confidence: 99%
“…The future research that will be based on the developed framework could assist development of better navigating strategies for autonomous drones or underwater vehicles, e.g. [31] or analysing sophisticated navigation strategies such as infotaxis [28], [27].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In order to evaluate the feasibility, accuracy and readiness of the current odor-based navigational models, there is a need for a framework that will enable an assessment of the variability of the proposed models. A unified framework and a computer simulation for quantitative comparison of the above mentioned models and others, similar to those proposed in autonomous navigation studies [1, 2931] is required.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using an insect antenna for robotic odour detection is its high temporal resolution owing to its short recovery time, along with its high sensitivity [17]. To overcome the slow recovery time of the semiconductor sensors, an algorithm using a system modelling approach of the sensor [18] or the derivative of the sensor output to decompose odour bouts has been developed [19] and implemented in small-sized drones for odour searching tasks [20,21]. Recent studies reported that some semiconductor gas sensors can resolve 2–5 Hz of odour pulses [21,22]; however, these values are still lower than the temporal resolution of insect antennae (more than 100 Hz [23]).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the slow recovery time of the semiconductor sensors, an algorithm using a system modelling approach of the sensor [18] or the derivative of the sensor output to decompose odour bouts has been developed [19] and implemented in small-sized drones for odour searching tasks [20,21]. Recent studies reported that some semiconductor gas sensors can resolve 2–5 Hz of odour pulses [21,22]; however, these values are still lower than the temporal resolution of insect antennae (more than 100 Hz [23]). The problem of using the EAG for robotic odour searching is that the measurement is strongly influenced by electrical and mechanical noises caused by robot movement, and the attenuation of odour signals because the antennal tissue dries and dies if the antenna is isolated.…”
Section: Introductionmentioning
confidence: 99%